Scaling algorithms in modelling of power loss in soft magnetic composites. Issue 4 (1st July 2019) - Najgebauer, Mariusz; Szczyglowski, Jan; Slusarek, Barbara; Przybylski, Marek
Abstract : Purpose: The purpose of this paper is to examine scaling algorithms in the description and modelling of power loss in soft magnetic composites (SMCs). Design/methodology/approach: Three scaling algorithms are examined to determine the most appropriate description of power loss in magnetic composites. The scaling coefficients are estimated in such a way that all measurement data should be collapsed onto a single curve, given in the scaled coordinates. The coefficient estimation is based on a non-linear optimization using the generalized reduced gradient method. The obtained formulae are then used in the power loss modelling. Findings: It is revealed that only two-component formulae are suitable for the scaling analysis of power loss because these allow obtaining of the collapse of measurement data. Research limitations/implications: This study considers just one type of SMC (Somaloy 700). Further research will be devoted to the verification of the scaling approach to the power loss modelling for other types of magnetic composites. Practical implications: The power loss is a basic property of soft magnetic materials, which determines their practical applications. The scaling approach to the power loss modelling gives quite simple models that require a reduced number of measurement data to estimate coefficients. Originality/value: The scaling algorithms can be a useful tool in the analysis and designing of magnetic circuits made of SMCs.